Scorpionism in children and adolescents: data from a sentinel unit (Research, Society and Development, 2021)
Objective: to analyze the epidemiological profile of scorpionic accidents in children and adolescents in a toxicological assistance center and to present the temporal behavior of the occurrences. Methods: cross-sectional, retrospective study, carried out at the Poison Control Center in Northwest Paraná. The sample consisted of notification forms for children and adolescents attended at the reference center from 2014 to 2018. 78 forms were analyzed using descriptive statistics and the Mann-Kendall test was used for trend analysis. Results: The majority of cases involved children up to five years old, male; most were classified as mild, and two evolved to death. There was an increase in cases in the period. Conclusion: there is a higher incidence in children under five years of age, and also an increasing number of cases over the period studied, which represents a serious public health problem in the studied municipality and region.